Ethnobotany of Lavandula × intermedia ’Abrialis’ in the Commune of Oulmès, Morocco - Radi, MOAHAMED; Drioiche, Aziz; El Balghiti El Alaoui, Asmaa; EL Menyiy, Naoual; El Ouadni, Hajar; Ayyad, Fatima Zahra; Eddamsyry, Brahim; Zibouh, Khalid; El Ouardi, Mohamed; Bousta, Dalila; Alaoui, Katim; El Imache, Ahde; et al. (Ethnobotany Research and Applications, 2025)
Background: The preservation of traditional knowledge about plant species is essential for their conservation and valorization. Lavandula × intermedia ’Abrialis’, a species widely cultivated in the Oulmès region of Morocco, is traditionally used for its medicinal properties. This study explores the local ethnobotanical knowledge associated with this plant in Oulmès, a region known for its longstanding use of lavender in traditional medicine. Methods: An ethnobotanical survey was conducted from March to June 2024 with 105 participants of diverse ages, genders, education levels, and socio-economic backgrounds. Data were collected using semi-structured questionnaires and analyzed using descriptive indicators such as Relative Frequency of Citation (RFC), Fidelity Level (FL), chi-square tests, and Multiple Correspondence Analysis (MCA). Results: The findings indicate that broncho-pulmonary ailments are the most commonly treated conditions, with the highest RFC (0.87) and FL (83.81%). Four primary usage categories emerged: medicinal (85.71%), cosmetic (66.67%), commercial (45.71%), and ecological (24.76%). Chi-square analysis showed no significant link between age and knowledge source, but significant associations were found with gender, socio-economic status, and education, emphasizing their roles in knowledge transmission. Conclusion: This study underscores the medicinal importance of L. × intermedia ’Abrialis’ in Oulmès and the value of preserving traditional plant knowledge. It also provides a foundation for future pharmacological research and supports the sustainable management of this species. Keywords: Medicinal plants, Lavandula × intermedia ’Abrialis’, Ethnobotanical study, Socio-economic, Traditional use, Oulmès, Morocco.